Factors Influencing the Quality of Online Teaching: Application of DEMATEL and Cluster Technology - Li, Ruining; Meng, Yichen (International Journal of Emerging Technologies in Learning (iJET), 2023)
With the informationization of higher education, colleges and universities can fully apply online teaching mode to education and teaching. Therefore, analysis of factors affecting teaching quality of college teachers in online teaching can effectively make evaluation object (teachers) have a sense of achievement and pride, so as to mobilize enthusiasm of evaluation object and to stimulate the consciousness of honor and shame and consciousness of competition. This study adopts application of DEMATEL and Cluster technology, conducts a questionnaire survey on 5 colleges and universities in Henan Province, analyzes and identifies the teachers’ factors among factors affecting teaching quality of E-commerce courses, and analyzes comprehensive influence index of teachers’ factors, namely impact degree, affected degree, cause degree and centrality degree. A cluster flight is carried out on evaluation results of students. Results show that X2-2, X2-4, X2-5, and X4-3 represent high degree of centrality and high degree of cause, that is high importance of factor and the cause factor. The results of teacher evaluation can be divided into three groups by the K-means clustering method, and the clustering group shows significant significance for all research items (p < 0.05). The weights of X2-2, X2-4, X2-5, and X4-3 in cluster analysis also rank the top four, which is highly consistent with the results of DEMATEL’s research, demonstrating that application of DEMATEL and Cluster technology proposed is very maneuverable and scientific. Research results have important reference value for improving online teaching strategy, improving the quality of online teaching, and regulating teaching activities as a whole through the use of online teaching quality evaluation.